Neutrosophic Inventory System for Decaying Items with Price Dependent Demand - R. Surya; M. Mullai; G. Vetrivel (Neutrosophic Sets and Systems, 2024)
This study presents an empirical investigation of a specific problem in inventory control, notably the manage-ment of decaying commodities with demand that is influenced by price. The approach taken in this research incorporatesthe effective use of trapezoidal neutrosophic numbers. The present model is employed for the objective of finding the neu-trosophic optimal total cost and neutrosophic optimal interval of time for the inventory system. Defuzzification process isdone with the help of signed distance method. Moreover, a mathematical evaluation is conducted in order to assess the statedmodel, and the findings are elucidated through the use of a numerical illustration.